Public-key code-based cryptography - Кузнецов, Олександр Олександрович; Пушкарьов, Андрій Іванович; Шевцов, Олексій Володимирович; Кузнецова, Тетяна Юріївна (Ukrainian Information Security Research Journal, 2016)
The possibility of a quantum computer threatens the existence of many asymmetric cryptographic primitives. An important advantage of code cryptosystems is the high resistance to the quantum cryptanalysis. Therefore it is in great demand increasing the speed of the code based primitives and their protection from classical cryptanalysis. Code-Based Public-Key Cryptosystems based on algebraic coding are considered in this paper. In addition, the current state, the existing contradictions and prospects of practical use for the post-quantum period are studied. We consider estimation of resistance to attack permutation decoding and computational complexity compared to the RSA scheme. We proposed a new code cryptosystem, it significantly increases the relative information performance and keeps the main advantages of resistance to classical and quantum cryptanalysis.